EFEKTIVITAS BELAJAR BAHASA ARAB BAGI SISWA MADRASAH IBTIDAIYAH MUTMAINNAH BATUALANG TAHUN AJARAN 2024/2025 - Fuji Kusuma Adynata (Yayasan Nusantara Hasana Berdikari, 2025)
Learning Arabic for students at the Mutmainnah Batualang Elementary School (MI) is crucial for providing a foundational understanding of Islam and broadening cultural horizons. This learning aims to equip students with Arabic language skills, including listening, speaking, reading, and writing. Learning Arabic for MI (Madrasah Ibtidaiyah) students is crucial for helping them understand Islamic teachings, particularly the Quran and Hadith. Learning Arabic from an early age, especially at MI, can establish a solid religious foundation in children and foster a positive attitude toward Arabic. This study employed descriptive qualitative research methods and data collection techniques using observation, interviews, and documentation. The conclusion of this study is that learning Arabic is often a daunting subject for students in schools and madrasas. Many students dislike Arabic lessons, despite the importance of Arabic in the Islamic world. However, many students still dislike Arabic lessons. Therefore, changes in the teaching of Arabic are needed. One of these is the need to change the teaching methods used to foster students' interest in Arabic. Once they are interested in Arabic, they will be able to participate enthusiastically without any coercion or pressure. This way, the Arabic learning process will proceed according to plan and students will absorb it easily and enjoyably.